2017
DOI: 10.1111/jan.13346
|View full text |Cite
|
Sign up to set email alerts
|

Nurse vs. physician‐led care for obstructive sleep apnoea: A systematic review and meta‐analysis of randomized trials

Abstract: Nurse-led care for adults with obstructive sleep apnoea is non-inferior to physician-led care. More research is needed to standardize nurse-led interventions and evaluate their long-term effectiveness and cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For asthma patients, there was comparable effect on number of exacerbations (Baker et al, 2017;Kuethe et al, 2013), quality of life, disease severity and symptoms as well as use of preventer medication (Baishnab et al, 2012;Kuethe et al, 2013) and levels of correct inhalation technique and wellcontrolled asthma (Martínez-González et al, 2015). Nurse-delivered home care and education for patients with obstructive sleep apnoea was shown to have no significant effect on continuous positive airway pressure and physical functioning compared with physician-delivered care (Gong et al, 2018).…”
Section: Martínezmentioning
confidence: 96%
“…For asthma patients, there was comparable effect on number of exacerbations (Baker et al, 2017;Kuethe et al, 2013), quality of life, disease severity and symptoms as well as use of preventer medication (Baishnab et al, 2012;Kuethe et al, 2013) and levels of correct inhalation technique and wellcontrolled asthma (Martínez-González et al, 2015). Nurse-delivered home care and education for patients with obstructive sleep apnoea was shown to have no significant effect on continuous positive airway pressure and physical functioning compared with physician-delivered care (Gong et al, 2018).…”
Section: Martínezmentioning
confidence: 96%
“…To date, sleep management strategies consisting of pharmacological, non‐pharmacological and surgical interventions have been reviewed (Videnovic, ). Critically, one systematic meta‐analysis and review demonstrated that nurse‐led care for sleep complaints is not inferior to physician‐led care (Gong et al., ). Here, we focused on non‐pharmacological therapies, more specifically, those that can be performed by Registered Nurses independently.…”
Section: Discussionmentioning
confidence: 99%
“…[37] Four studies found no difference in outcomes with nurse and physician-led care of obstructive sleep apnoea. [38] A Cochrane review, comprising two studies assessing accuracy of nurse-led preoperative assessment (historically assigned to doctors), found no evidence of difference in performance or cost. [39]…”
Section: Substitution From Doctors To Nursesmentioning
confidence: 99%